The Cradle of Ice: Moonfall #2 - Rollins, James, 1961- (New York : Tor, Tor Publishing Group, 2023)
"The second book in the New York Times bestselling Moonfall series from thriller-master James Rollins, The Cradle of Ice is a page-turning tale of action, adventure, betrayal, ambition, and the struggle for survival in a harsh world that hangs by a thread. To stop the coming apocalypse, a fellowship was formed. A soldier, a thief, a lost prince, and a young girl bonded by fate and looming disaster. Each step along this path has changed the party, forging deep alliances and greater enmities. All the while, hostile forces have hunted them, fearing what they might unleash. Armies wage war around them. For each step has come with a cost-in blood, in loss, in heartbreak. Now, they must split, traveling into a vast region of ice and to a sprawling capital of the world they've only known in stories. Time is running out and only the truth will save us all. The Moonfall Series: The Starless Crown The Cradle of Ice"--.
new book 2023 spring.
Keywords: Quests (Expeditions); End of the world; Dystopian fiction; Fantasy fiction; Alliances; Outcasts; apocalyptic & post apocalyptic fiction